PENGARUH LAMA PENGOMPOSAN SERBUK GERGAJI KAYU JATI DAN DOSIS EM4 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA ( Brassica oleracea L . ) DATARAN RENDAH - Sri Hariningsih Pratiwi; Retno Tri Purnamasari (Universitas Tribhuwana Tunggadewi, 2018)
This research was purposed to find out whether there was any significant correlation of the composting time of teak sawdust and EM4 dose on the growth and yield of lowland flower cabbage plants or not. This research was carried out at the Experimental Field of Universitas Merdeka Pasuruan (Sultan Agung Street), Pasuruan City at an altitude of 4 m-asl. This research used factorial Randomized Block Design (RBD) method consisted of two factors and repeated three times. The first factor was the length of composting (L) with L1: one month, L2: two months and L3: three months. The second factor was the dose of EM4 (D) with D1 : 10% EM4 dose, D2 : 20% EM4 dose and D3: 30% EM4 dose. Overall there were nine combinations of treatments. The results showed that there was 20% EM4 dose with a 2 months composting time yielded higher results on all observed parameters. Flower cabbage with a dose of 20% EM4 with composting time of 2 months produced fresh weight of 15.97 tons ha-1, at a dose of EM4 20% with a composting time of 1 month produced fresh weight 13.86 tons ha-1, while the lowest yield at dose of 20% EM4 with a composting time of 3 months produced fresh weight 9.79 tons ha-1.